The invisible evil twin of an adrenal adenoma / Aimi Fadilah M … [et al.] - Mohamad, Aimi Fadilah; Mohamed Shah, Fatimah Zaherah; Zainordin, Nur Aisyah; Eddy Warman, ur 'Aini; Ab Mumin, Nazimah; Omar, Effat; Abdul Ghani, Rohana (Universiti Teknologi MARA Cawangan Selangor, 2019)
Primary aldosteronism (PA) causes a persistently elevated blood pressure (BP) due to excessive release of the hormone aldosterone from the adrenal glands. Classically, it is called Conn’s syndrome and is described as the triad of hypertension and hypokalemia with the presence of unilateral adrenal adenoma. It can be cured with surgical resection of the aldosterone-secreting adenoma leading to resolution of hypertension, hypokalemia and increased cardiovascular risk associated with hyperaldosteronism. We present a case of a man with previous ischemic heart disease (IHD) who presented with resistant hypertension. Investigations for secondary causes of hypertension revealed an elevated aldosterone level and saline suppression test confirmed the diagnosis of PA. Radiological examination revealed a left adrenal adenoma and a normal right adrenal gland. However, adrenal venous sampling showed lateralization of aldosterone secretion towards the right. He subsequently underwent a laparoscopic right adrenalectomy which improved his BP control promptly. This case highlights the importance of recognizing the need to investigate for secondary causes of hypertension. It also underscores the importance of dynamic tests, which may not be easily accessible to most clinicians but should pursue, to allow a definitive diagnosis and effective treatment.